Palliative care and imaging utilisation for patients with cancer. Issue Volume 12:Issue e6(2022) (1st March 2019) - Raghavan, Kesav; Copeland, Timothy P; Rabow, Michael; Ladenheim, Maya; Marks, Angela; Pantilat, Steven Z; O'Riordan, David; Seidenwurm, David; Franc, Benjamin
Abstract : Objective: This observational study explores the association between palliative care (PC) involvement and high-cost imaging utilisation for patients with cancer patients during the last 3 months of life. Methods: Adult patients with cancer who died between 1 January 2012 and 31 May 2015 were identified. Referral to PC, intensity of PC service use, and non-emergent oncological imaging utilisation were determined. Associations between PC utilisation and proportion of patients imaged and mean number of studies per patient (mean imaging intensity (MII)) were assessed for the last 3 months and the last month of life. Similar analyses were performed for randomly matched case-control pairs (n = 197). Finally, the association between intensity of PC involvement and imaging utilisation was assessed. Results: 3784 patients were included, with 3523 (93%) never referred to PC and 261 (7%) seen by PC, largely before the last month of life (61%). Similar proportions of patients with and without PC referral were imaged during the last 3 months, while a greater proportion of patients with PC referral were imaged in the last month of life. PC involvement was not associated with significantly different MII during either time frame. In the matched-pairs analysis, a greater proportion of patients previously referred to PC received imaging in the period between the first PC encounter and death, and in the last month of life. MII remained similar between PC and non-PC groups. Finally, intensity of PC services was similar for imaged and non-imaged patients in the final 3 months and 1 month of life. During these time periods, increased PC intensity was not associated with decreased MII. Conclusions: PC involvement in end-of-life oncological care was not associated with decreased use of non-emergent, high-cost imaging. The role of advanced imaging in the PC setting requires further investigation.